Advances Systematic Literature Review (SLR): Kemajuan Teknik Lapisan Semprot Pada Sel Surya Ditinjau dari Aspek Efisiensi dan Prospek Komersialisasi - Kurniawan, Adi; Indriawati, Anisa (Jurusan Fisika, Universitas Bangka Belitung, 2024)
This systematic review examines recent developments in spray-coated solar cells through analysis of 127 peer-reviewed studies (2019-2024). Our findings highlight significant advances in ultrasonic spray techniques, achieving thickness variations of ±2.5% and perovskite-based device efficiencies reaching 21.7%. Large-scale implementation demonstrated successful coating areas of 1.5 m² while maintaining 90% of lab-scale performance. Despite promising results, stability remains challenging, with typical efficiency losses of 15-20% over 1000 hours. Current trends suggest commercial viability within 3-5 years, contingent upon advances in materials and processing techniques.